Cosmological Subjectivities: Exploring 'Truth' Environmentalities in the Haa Highlands of Bhutan - Jesse Montes (Conservation & Society, 2020)
This paper explores local perceptions of the landscape in a small highland community near Haa, Bhutan. Through the lens of ethnoecology, it documents a storied landscape in which an animist cosmology, underpinned by Buddhism, shapes local subjectivities in particular ways that influence behaviour in relation to this landscape. We draw on this case to contribute to a growing body of research exploring how environmental governance understood as Foucauldian-inspired 'environmentality' works to create 'environmental subjects'. While initial work in this area describes a monolithic environmentality, more recent research outlines multiple environmentalities (neoliberal, disciplinary, sovereign and truth) to demonstrate how processes of subject formation occur differently in relation to each of these. Within this research, however, attention to truth environmentality and the particular forms of environmental subjectivity it cultivates has been largely absent thus far. Our analysis addresses this gap by exploring how members of the herding community in the case under investigation describe relationships with a set of cosmological entities that motivate specific self-understandings leading to conservation-conducive behaviour. In this way, our analysis highlights how this particular approach to the 'conduct of conduct' works to shape specific environmental subjectivities beyond those currently highlighted in the burgeoning environmentalities literature.